2020
DOI: 10.18203/2320-1770.ijrcog20204304
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors associated with ectopic pregnancy in our sociodemographic setup

Abstract: Background: Ectopic pregnancy (EP) is assuming greater importance because of its increasing incidence and its impact on woman’s fertility.Aim: To assess the frequency and to determine an association between the studied risk factors and ectopic pregnancy.Methods: A retrospective study was conducted for the role of several risk factors in the occurrence of EP in department of obstetrics and Gynaecology, SMGS Hospital. A total of 110 cases and 110 controls were compared for socio demographic characteristics, ciga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 16 publications
(26 reference statements)
2
4
0
Order By: Relevance
“…7 21,22 We observed that patients with endometriosis were more prevalent in cases (11.7% vs. 1.7%; p-value=0.028), indicating that endometriosis has an association with ectopic pregnancy, which is in consonance with study of Jobspira N et al, Gandotra et al and Hunter RHF. 7,23,24 In the present study, we found that infertility was more common among patients with ectopic pregnancies (18.3% vs. 3.3%; p-value=0.008*), Tuomivaara and Ronnberg have assessed 929 infertile couples with regard to ectopic pregnancy in a follow-up investigation. Their research revealed rates of 46% for conception and 9% for ectopic pregnancies, respectively.…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…7 21,22 We observed that patients with endometriosis were more prevalent in cases (11.7% vs. 1.7%; p-value=0.028), indicating that endometriosis has an association with ectopic pregnancy, which is in consonance with study of Jobspira N et al, Gandotra et al and Hunter RHF. 7,23,24 In the present study, we found that infertility was more common among patients with ectopic pregnancies (18.3% vs. 3.3%; p-value=0.008*), Tuomivaara and Ronnberg have assessed 929 infertile couples with regard to ectopic pregnancy in a follow-up investigation. Their research revealed rates of 46% for conception and 9% for ectopic pregnancies, respectively.…”
Section: Discussionsupporting
confidence: 88%
“…16 The risk of ectopic pregnancy was also found to increase among patients with lower socioeconomic status (56% vs 13.3%; p-value0.001), which is consistent with multitude of studies due to Gandotra et al, Yuk et al and Aboyeji et l, who reported that lower socio-economic status was more prevalent among patients with ectopic pregnancies. 7,17,18 In the present study, we found that patients with history of abortions were more common in cases compared to controls (23.3% vs. 8.3%;p-value=0.024*), which infers that history of abortions play a significant role in the development of ectopic pregnancies. Much similar observations have been reported by Gndotra et al, Tharaux-Beneux et al and Bouyer et a, who reported a significant association between history of abortions and ectopic pregnancies.…”
Section: Discussionsupporting
confidence: 56%
See 2 more Smart Citations
“…Gandotra et al found that although contraceptive methods like barrier and oral contraceptives was found to lower the risk, contraceptive methods like POP (OR 7.19) and IUCD (OR 3.55) were found to increase the risk for ectopic pregnancy. 23 Emergency contraception use in current pregnancy accounted for 2% of ectopic pregnancy in present study. Jain et al found that hormonal emergency contraceptive pills failure rate is high when used in periovulatory period with increased chance of EP.…”
Section: Discussionmentioning
confidence: 54%